1988
DOI: 10.1128/jcm.26.5.933-937.1988
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpes simplex virus DNA from genital lesions by in situ hybridization

Abstract: Lesion specimens from 118 episodes of recurrent genital herpes were used to compare herpes simplex virus (HSV) isolation with a direct specimen test for in situ DNA hybridization utilizing a biotinylated probe. The frequency of detection of HSV was similar with both tests; HSV was isolated from 81% of vesicular lesions, 76% of pustules, and 67% of ulcers, while HSV DNA was detected in 77, 76, and 55% of lesions in these stages, respectively. Utilizing both methods, HSV was identified in 91, 94, and 79%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Viral cultures have been considered the gold standard for -HSV identification; however, this method typically takes several days to a week, although coupling culture with several antigenic or hybridization detection techniques have been evaluated as an alternative approach for rapid diagnosis (4). Nonisotopic in situ hybridization (ISH) techniques performed directly on tissue and cytologic specimens are an attractive possibility as they require as little as 1-2 hr to perform and may be comparable to viral cultures in sensitivity (5).…”
Section: Introductionmentioning
confidence: 99%
“…Viral cultures have been considered the gold standard for -HSV identification; however, this method typically takes several days to a week, although coupling culture with several antigenic or hybridization detection techniques have been evaluated as an alternative approach for rapid diagnosis (4). Nonisotopic in situ hybridization (ISH) techniques performed directly on tissue and cytologic specimens are an attractive possibility as they require as little as 1-2 hr to perform and may be comparable to viral cultures in sensitivity (5).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of viral DNA probes has modified considerably the diagnosis of viral infections (3,4,11,15,19,29,33). Our intention was to adapt ISH methodology to 96microwell microplates and especially to apply this methodology to the research of infectious CMV isolated by cell culture, i.e., after inoculation of MRC-5 fibroblasts with biological specimens.…”
mentioning
confidence: 99%
“…Quicker, if somewhat less sensitive, results can be obtained by various nonculture techniques. These include the cytological examination of lesion cells by Wright-Giemsa stain (Tzanck preparation) (3,17), the use of fluorescein-conjugated HSV antibodies in a direct immunofluorescence test (14), immunoperoxidase staining (6,14), direct enzyme immunoassay (EIA) (7,10), and DNA hybridization (4,8).…”
mentioning
confidence: 99%
“…That SC-HSV was found to be more sensitive for vesicular lesions and for first-episode genital HSV infections is not surprising. It has been shown that the ability to detect HSV (antigen) varies over the course of the disease, and viral titers have been found to be highest in the vesicular stages of the disease (6,8,11). Also, first episodes of genital herpes often have higher viral titers and a longer duration of virus shedding (1,6).…”
mentioning
confidence: 99%